Inclusive pedagogies for early childhood education respecting and responding to differences in learning - Conn, Carmel; Murphy, Alison (London Routledge, Taylor & Francis Group, 2022)
"This essential textbook explores inclusive pedagogies by presenting theoretical viewpoints and research on everyday practices in early childhood education that affirm diversity in relation to learning, disability and culture. The authors consider the pedagogical practices involved in supporting educational inclusion for young children. The book focuses on key issues in relation to inclusive pedagogy including young children's learning subjectivities, socio-material realities of learning in early childhood contexts, and perspective-taking of children and adults in relation to learning and difference. The book draws together findings from experts who are employing innovative methods for research in early childhood education, including conversation analysis, phenomenological enquiry and participant ethnography, in order to create new knowledge and understanding about how young children are and feel themselves to be included. This textbook will be essential reading for students and practitioners alike. The book is particularly pertinent for undergraduate and post graduate students studying early years as well as courses which focus on education or teaching or inclusion"
Introduction : inclusive pedagogy as an ethics of responsibility and care / Carmel Conn and Alison Murphy -- The children's rights approach to early childhood education : policy and context in Wales / Alison Murphy and Jane Waters-Davies -- Placing inclusion at the heart of things : the 'tricky challenge' for educational leadership / Matt Hutt -- Seeing children's learning subjectivities for inclusive pedagogy in early childhood education / Carmel Conn -- Children's agency and negotiation of space for enabling environments : the use of tuff spots for practitioner education / Claire Pescott -- Socialising a pedagogy of care in a New Zealand early childhood refugee centre / Amanda Bateman and Linda Mitchell -- Social embodiment in early childhood education for children with PMLD / Ben Simmons -- Foundation phase teachers' understandings and enactment of participation in school settings in Wales / Alison Murphy, Jacky Tyrie, Jane Waters-Davies, Sarah Chicken and Jennifer Clement -- Using an environmental affordance perspective to consider children's 'challenging behaviour' in the classroom and at forest school / Angela Rekers -- Inclusion, participation and interaction : challenging the discourse of in-class ability groupings in early childhood education / Eleri John -- The capable child as a threshold concept for inclusive early childhood education and care / Jane Waters-Davies and Natalie McDonald.
Includes bibliographical references and index.
Keywords: Inclusive education; Early childhood education; Children with disabilities -- Education (Early childhood)